On the Search for Something New - Innovation and Brainstorming shaping Business Models - Pilas, Jacek (My University, 2008)
The purpose of this paper is to present and emphasize an enormous impact of innovation in businesses models in the modern competitive global market. The World has been changing rapidly over last few decades. The competition among market leaders is no longer changing existing product or services but moving firms away from “Red Ocean” into “Blue Ocean”. There is a widespread recognition that competition between businesses today is not solely based on their competitive strategy but on their business models. The first step into profound changes is to analyze company’s paradigm and describe precisely c ore competence. Furthermore, a sustainable competitive position can be reached only when a company is able to innovate its business concept - its business model. Scientists claim that innovation is like spring after winter. If company wants to exist on the market it has to innovate. Companies today are engaging in “strategic benchmarking”, that is learning from the best practices entailed in the innovative business models of companies in a wide variety of industries in different countries. Researchers do not consider innovation as an entirely new phenomenon. Jan Fagerberg wrote in his book that it is as old as mankind itself. Thinking about something new and better ways or solutions seems to be in our human nature. The fact is that scientists, CEO’s and economists have not discovered its importance. As a student of FHS Kufstein in Austria I had an opportunity to attend a course: Innovative Business Models. I was inspired by my former professor Dr. Guillermo Duenas who presented me the newest trends in business world. Some people think there is too much talking about innovation, it became “trendy topic”, if you want to be trendy just start talking about innovation. In my opinion it is trendy but only proper understanding of what is really business model, its design and innovation and the Blue Ocean Strategy can be helpful in achieving success in business. I want it to be practical handout in stick to the essentials.
Szukając nowych rozwiązań - Innowacja i Brainstorming nadające kształt modelom biznesowym ﻿
Keywords: business models; innovation; brainstorming